Caracterización en banda ancha de la constante de propagación de materiales de impresión 3D - Pérez-Escribano, Mario; Márquez-Segura, Enrique (My University, 2020)
In this work, a method for the characterization of the relative permittivity in broadband of 3D printing materials is proposed. It uses microstrip lines of different lengths covered with the material to be characterized. Once S-parameters of the structure are obtained, some transformations are performed, using transmission parameters and the line length differences, in order to obtain the propagation constant of the lines, from which it is possible to extract the characteristics of the material to be studied. The method has been tested by manufacturing and measuring lines covered with ABS material, showing results very close to those of electromagnetic simulation and those shown in the literature for this material.
Keywords: Impresión tridimensional; Fabricación aditiva; FDM; Polímero; Caracterización; Permitividad